Cambridge global English activity book stage 1 - Linse, Caroline; Schottman, Elly (New York : Cambridge, 2014)
The Activity Book complements the Stage 1 Learner's Book by providing additional practice activities that reinforce language skills and content introduced in the Learner's Book. It contains nine thematic units, each corresponding with the topics, texts, and language input of the Learner's Book. Each lesson in the Learner's Book is supported by two pages in the Activity Book. Learning is reinforced through activities framed within the 'I can' objectives of the course, opportunities for personalization and creative work, and a higher level of challenge to support differentiation. Each unit ends with a quiz, offering more in-depth assessment for learners. The book is aligned with the Common European Framework of Reference (CEFR) at a level towards A1.
Keywords: Language Learning -- Activity Book -- Cambridge Curriculum